Answer:
No, these functions fail to be inverses of each other.
Explanation:
We have two functions :
- f(x) = 3x + 2
- g(x) =
![(x-2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/aadvb1m5beiqhb0m8q7ohk2crg2bm1n91c.png)
Let's take the function f(x) and take x = 1.
- f(1) = 3(1) + 2
- f(1) = 5 [Keep this in mind]
- If f(1) is 5, then if g(x) is an inverse function, g(1) should be
![(1)/(5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/u5y4nnciiyc0ftq4somvdfvrab3jg27j4z.png)
Let's try the same with g(x).
- g(1) =
![(1-2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ghuxinm8b9rhsbn45zjgmiah0q3xgfkq1x.png)
- g(1) =
![-(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/getquuff49cohne05n98hv73iv77n9lzv4.png)
Clearly, they are not inverse functions of each other.